Pemanfaatan Website Sebagai Media Promosi Dan Meningkatkan Peserta Didik Pada (Ma) Madrasah Aliyah Ibrohimiyyah Demak: Pemanfaatan Website Sebagai Media Promosi Dan Meningkatkan Peserta Didik Pada (Ma) Madrasah Aliyah Ibrohimiyyah Demak - Febryantahanuji, Febryantahanuji (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2017)
The development of information technology is growing rapidly, especially for business interests and promotion of a product or company. Do not miss like a company. Also in the world of education, this becomes a significant impact in the field of education to continue to show its existence in the world of technology. In the development of information technology, especially the Internet that can cause a sense of interest and curious because the internet can make many people do not feel easily saturated, with the internet we can easily to open a window of information fast and current. So there is no harm in some agencies began to use the website. With any website can promote an agency method is not directly related to information technology, one way is to utilize the website as a marketing and promotional media. It is hoped that MA Ibrohimiyyah can use the website to improve the promotion of institutions and learners. With the promotion website will not be limited by place and time. So it is expected to improve students in accordance with the expectations of the institution.